Long-term effectiveness of a lifestyle intervention for rheumatoid arthritis and osteoarthritis: 1-year follow-up of the ‘Plants for Joints’ randomised clinical trial - Jos W R Twisk; Maarten Boers; Dirkjan van Schaardenburg; Franktien Turkstra; Henriët van Middendorp; Martijn Gerritsen; Marike van der Leeden; Martin Van der Esch; Carlijn A Wagenaar; Wendy Walrabenstein; Peter J M Weijs (RMD Open)
Objectives In two randomised controlled trials, the Plants for Joints (PFJ) multidisciplinary lifestyle intervention reduced signs and symptoms of rheumatoid arthritis (RA), or metabolic syndrome-associated hip or knee osteoarthritis (MSOA) compared with usual care. The current study investigated long-term outcomes.Methods After completion of two 16-week trials in people with (1) RA or (2) MSOA, control groups switched to the active PFJ intervention. At the end of the intervention, all participants were followed up in a 1-year observational extension study. Primary outcomes were 28-joint Disease Activity Score (DAS28) (RA) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) (MSOA). Secondary outcomes included body composition, metabolic outcomes, medication changes and intervention adherence. An intention-to-treat analysis with a linear mixed model was used to analyse within-group changes.Results 65 (84%) of 77 RA participants and 49 (77%) of 64 MSOA participants completed the extension study. The effects of the PFJ intervention were replicated in the original control groups and sustained within the RA group a year after intervention completion (mean DAS28 –0.9 points; p<0.001), while in the MSOA group mean WOMAC increased towards but remained well under the starting value (–7.8 points, p<0.001). Improvements in C-reactive protein, waist circumference (RA and MSOA); low-density lipoprotein cholesterol (RA); and weight, haemoglobin A1c, blood pressure (MSOA) were also sustained. Participants had a net decrease of medication, and intervention adherence was largely sustained.Conclusions A year after the PFJ lifestyle intervention, improvements of disease activity and metabolic outcomes within RA and MSOA groups were largely sustained and related to sustained adherence, with a net decrease of medication.Trial registration numbers NL7800, NL7801.